2017
DOI: 10.1016/j.aap.2016.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian self-reported use of smart phones: Positive attitudes and high exposure influence intentions to cross the road while distracted

Abstract: Pedestrian crashes are an important issue globally as pedestrians are a highly vulnerable road user group, accounting for approximately 35% of road deaths worldwide each year. In highly motorised countries, pedestrian distraction by hand held technological devices appears to be an increasing factor in such crashes. An online survey (N=363) was conducted to 1) obtain prevalence information regarding the extent to which people cross the road while simultaneously using mobile phones for potentially distracting ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 35 publications
5
37
1
4
Order By: Relevance
“…The current sample also had a lower proportion of men than women which may limit its generalisability to the wider male population. However, the proportion seems typical to similar studies in Queensland [ 44 ]. Next, although this study assessed both psychological and physiological personal variables, there are other environmental variables that influence mobile phone usage while driving, such as heavy traffic and urbanization [ 29 ].…”
Section: Limitationssupporting
confidence: 64%
“…The current sample also had a lower proportion of men than women which may limit its generalisability to the wider male population. However, the proportion seems typical to similar studies in Queensland [ 44 ]. Next, although this study assessed both psychological and physiological personal variables, there are other environmental variables that influence mobile phone usage while driving, such as heavy traffic and urbanization [ 29 ].…”
Section: Limitationssupporting
confidence: 64%
“…The demanding manual process of using a smartphone also impairs a driver’s performance by removing one or both hands from the steering wheel (i.e., manual distraction) ( Head, Helton, Russell, & Neumann, 2012 ). Finally, these three types of distractions can be accompanied by cognitive interferences that take the user’s mind off of his/her current activity (e.g., causing cognitive distraction) ( Lennon, Oviedo-Trespalacios, & Matthews, 2017 ; Young, 2012 ). Furthermore, due to the multi-functioning features of smartphones, using a smartphone can concurrently produce these distractions, thereby increasing the risk of accidents ( Shah, 2002 ; Young & Salmon, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study of 405 university students found that there was a perception that they could compensate for the negative effect of mobile phone distractions while crossing (Jiang et al, 2016). These studies are suppported by evidence from studies of teenagers (13 to 18 years) that found teens were at high risk because of frequent use of mobile phones while walking, and group norms encourage mobile phone use while crossing the road (Lennon et al, 2017).…”
Section: Limitations and Further Researchmentioning
confidence: 99%